UPAYA MENINGKATKAN KEMAMPUAN MEMBACA MELALUI METODE SCRAMBLE PADA PESERTA DIDIK KELAS I SD NEGERI 002 BENTENG KECAMATAN SUNGAI BATANG - Reni Marlina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
This study aims to improve students' reading ability through the first grade scramble students of SD Negeri 002 Benteng, Kecamatan Sungai Batang, which are 28 students with 11 male students and 17 female students with heterogeneous ability. This study is based on the low ability of students' learning outcomes and lack of awareness of teachers to implement an effective, innovative, and cooperative learning. The study was conducted from September 3, 2016 to October 8, 2016. This study is a classroom action research (PTK) consisting of two cycles. Minimum completeness criteria (KKM) and average analysis are used to determine whether or not improvement of student learning outcomes before and after using the scramble learning model. The results of this study indicate that the number of students who reach KKM in the initial data is only 10 people (36%), cycle I is 16 people (57%), and the second cycle is 25 people (89%). The average student score at baseline was 68.4; cycle I increased to 75,9; in the second cycle increased again to 83,6. Based on the results of this study it can be concluded that the model of learning scramble can improve reading ability in Indonesian language students class I of SD Negeri 002 Benteng, Kecamatan Sungai Batang.